Pengaruh Sosial Media Marketing Dan Destination Image Terhadap Minat Berkunjung Ke Kebun Raya Bogor - Andiaresmi, Putrityatami; Pramono, Rudy (Jayapangus Press, 2023)
The relationship between social media marketing, destination image and interest in visiting is very important in the tourism industry. Social media marketing can help create and maintain a positive destination image, which in turn will influence potential tourists' interest in visiting. This research aims to investigate the influence of two key factors, namely social media marketing and Destination Image, on visitors' interest in visiting the Bogor Botanical Gardens. This research uses a quantitative approach to measure the impact of these variables on visitor interest. This research uses quantitative methods with survey techniques. Data was collected through questionnaires distributed to visitors to the Bogor Botanical Gardens. The research sample was chosen randomly, and the total number of respondents involved was around 300 people. Data analysis was carried out using a simple linear regression test using SmartPLS. The results of data analysis show that social media marketing has a significant positive influence on interest in visiting the Bogor Botanical Gardens. Apart from that, Destination Image also has a significant positive influence on interest in visiting. Furthermore, this research shows that there is an interaction between social media marketing and destination image, meaning that the combination of the two can increase visitor interest more than either factor could produce individually. The results of this research show that social media marketing and destination image have a significant role in influencing visitors' interest in visiting the Bogor Botanical Gardens. In conclusion, the management of the Bogor Botanical Gardens and related parties can utilize social media marketing to promote this destination more effectively. Apart from that, efforts to improve the destination's image can also support increased visitor interest.